The 12-hour art expert : everything you need to know about art in a dozen masterpieces - Charney, Noah (Rowman & Littlefield, 2022)
"His novel, The Art Thief, was a bestseller in five countries and is translated into 17 languages. His The Art of Forgery, Stealing the Mystic Lamb and Slovenology were international bestsellers. His book Collector of Lives: Giorgio Vasari and the Invention of Art was nominated for the Pulitzer Prize. Charney is now a professor at University of Ljubljana in Slovenia, where Charney has lived for many years"--